2014
DOI: 10.2478/s13380-014-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation modulates left premotor cortex activity in facial expression recognition as a function of anxiety level

Abstract: Recognition of emotional facial expressions is based on simulation and mirroring processes, and the premotor cortex is supposed to support this simulation mechanism. The role of this prefrontal area in processing emotional faces with different valence (anger, fear, happiness and neutral) was explored taking into account the effect of the lateralization model (more right-side activation for negative emotions; more left-side activation for positive emotions) of face processing and anxiety level (high vs low). Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It also depends on somatosensory and motor areas that internally simulate the observed emotion, and that this process aids expression recognition (Niedenthal, 2007). This has been causally demonstrated in TMS studies that delivered TMS over the left premotor cortex (Enticott et al, 2008, Balconi et al, 2014. Rochas et al (2013) also reported that TMS delivered over the left presupplementary motor area (pre-SMA) selectively impaired the recognition of happy faces but not fearful or angry faces.…”
Section: Tms Studies Of Facial Expressionmentioning
confidence: 90%
See 1 more Smart Citation
“…It also depends on somatosensory and motor areas that internally simulate the observed emotion, and that this process aids expression recognition (Niedenthal, 2007). This has been causally demonstrated in TMS studies that delivered TMS over the left premotor cortex (Enticott et al, 2008, Balconi et al, 2014. Rochas et al (2013) also reported that TMS delivered over the left presupplementary motor area (pre-SMA) selectively impaired the recognition of happy faces but not fearful or angry faces.…”
Section: Tms Studies Of Facial Expressionmentioning
confidence: 90%
“…This is, at least partly, because many of the brain areas involved in processing expressions are located on the lateral brain surface and can be directly stimulated with TMS. TMS studies of expression processing have targeted the OFA (Pitcher et al, 2008), the posterior STS (Pourtois et al, 2004, Sliwinska and Pitcher, 2018, Sliwinska et al, 2020b, premotor cortex (Balconi et al, 2014), the face area in the somatosensory cortex (Pitcher et al, 2008), medial prefrontal cortex (Mattavelli et al, 2013), dorsolateral prefrontal cortex (Zwanzger et al, 2014) and the cerebellum (Ferrari et al, 2018). The fact that expressions are processed across so many areas distributed across the brain demonstrates the saliency of the face when conveying emotion.…”
Section: Tms Studies Of Facial Expressionmentioning
confidence: 99%